2013
DOI: 10.1016/j.legalmed.2013.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of some problematic factors in facial image identification using a 2D/3D superimposition technique

Abstract: The number of criminal cases requiring facial image identification of a suspect has been increasing because a surveillance camera is installed everywhere in the city and furthermore, the intercom with the recording function is installed in the home. In this study, we aimed to analyze the usefulness of a 2D/3D facial image superimposition system for image identification when facial aging, facial expression, and twins are under consideration. As a result, the mean values of the average distances calculated from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 11 publications
0
21
0
Order By: Relevance
“…Atsuchi et al. and Ogawa et al. reported that 3D images provide more reliable landmark placements as the structure can be more accurately observed in 3D.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Atsuchi et al. and Ogawa et al. reported that 3D images provide more reliable landmark placements as the structure can be more accurately observed in 3D.…”
Section: Discussionmentioning
confidence: 99%
“…Analyses were only performed on the frontal and lateral views of the face, without reflecting diverse angles . In addition, the reasons why the landmarks were used in facial mapping were not clearly explained . The landmarks associated with the ears have not thoroughly been investigated, although they have a high degree of individuality in terms of morphology .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Morphological profiles within and between populations and sexes (Kau et al, 2010), visualising soft tissue changes following orthognathic surgery (Miller, Morris and Berry, 2007), syndrome diagnosis (Shaweesh, Clement, Thomas and Bankier, 2006), facial growth (Nute & Moss, 2000) and facial aging (Atsuchi, Tsuji, Usumoto, Yoshino and Ikeda, 2013) have been studied.…”
Section: Facial Analysismentioning
confidence: 99%
“…Although the 2D/3D superimposition method is extremely useful [12][13][14][19][20][21], it cannot completely substitute for traditional methods. 3D facial images cannot always be obtained from a possible offender in every forensic case.…”
Section: Introductionmentioning
confidence: 99%